Temperature dependence of trapping effects in metal gates/Al2O3/InGaAs stacks - Palumbo, Félix Roberto Mario (2017)
The influence of the temperature on Metal Gate/Al2O3/n-InGaAs stacks has been studied by means of capacitance-voltage (C-V) hysteresis and flat band voltage as function of both negative and positive stress fields. It was found that the de-trapping effect decreases at low-temperature, indicating that the de-trapping of trapped electrons from oxide traps may be performed via Al2O3/InGaAs interface defects.The dependence of the C-V hysteresis on the stress field at different temperatures in our InGaAs stacks can be explained in terms of the defect spatial distribution. An oxide defect distribution can be found very close to the metal gate/Al2O3 interface. On the other side, the Al2O3/InGaAs interface presents defects distributed from the interface into the bulk of the oxide, showing the influence of InGaAs on Al2O3 in terms of the spatial defect distribution.